Comparison of Biogenic Amines and Mycotoxins in Alfalfa and Red Clover Fodder Depending on Additives - Skladanka, Jiri; Adam, Vojtech; Zitka, Ondrej; Mlejnkova, Veronika; Kalhotka, Libor; Horky, Pavel; Konecna, Klara; Hodulikova, Lucia; Knotova, Daniela; Balabanova, Marie; Slama, Petr; Skarpa, Petr (International journal of environmental research and public health, 2017)
In the production of fermented feed, each crop can be contaminated with a variety of microorganisms that may produce natural pollutants. Biogenic amines, mycotoxins, and undesirable organic acids can decrease health feed safety. The aim of this study was to compare the counts of microorganisms, levels of biogenic amines, and the mycotoxins in forage legumes, and also to compare the occurrence of microorganisms and levels of mycotoxins in green fodder and subsequently produced silage and the influence of additives on the content of natural harmful substances in silage. The experimental plot was located in Troubsko and Vatín, in the Czech Republic. Two varieties of Medicago sativa and one variety of Trifolium pratense were compared. Green fodder and subsequently produced silage reaching up to 23% of dry matter were evaluated and prepared using a bio-enzymatic additive and a chemical additive. Green fodder of Medicago sativa was more contaminated by Enterococci than Trifolium pratense fodder. The obvious difference was determined by the quality of silage leachate. The silage prepared from Medicago sativa fodder was more contaminated with butyric acid. Fungi were present in higher counts in the anaerobic environment of green fodder and contaminated it with zearalenone and deoxynivalenol. Lower counts of fungi were found in silage, although the zearalenone content did not change. Lower content of deoxynivalenol was detected in silage, compared with green fodder. Silages treated with a chemical additive were found not to contain butyric acid. Lower ethanol content was determined, and the tendency to reduce the risk of biogenic amines occurrence was evident. The additives proved to have no influence on the content of mycotoxins.
Keywords: Food Additives; chemical additives; zearalenone; Biogenic Amines; fermentace; biogenní aminy; Animal Feed; biological additives; tyramine; enterococci; green matter; mykotoxiny; putrescine; Mycotoxins; potravinářské přísady; Silage; spermine; zvířata; silage; siláž; Fermentation; butyric acid; krmivo pro zvířata; kontaminace potravin; deoxynivalenol; Food Contamination; Trifolium; Czech Republic; Medicago sativa; cadaverine; Animals; Česká republika; fungi